Bens patrimoniais e escolas públicas: uma aproximação necessária - Gominho Filho, Fortunato Ferraz (2006)
The present thesis emphasises the need for an aproach among public education instituitions and listed heritage through an analytic conception. It also focuses the enhancement of a dormant identity among students and the heritage, developing their knowledge, skill, attitude and proper evaluation through the teaching of its significance. As shown in the survey of teachers of some units of Pedro II High School, students affiliated to the PIC-JUNIOR program, a joint commitment with the National Museum, authorities and officials of both instituitions allocated for contact with the public on the construction and listed parks, the activity motivates opinions and concern required to debate the enhancement of the heritage as an educational instrument. Along the same way, mapping expresses the concern of students, teachers and authorities as for the need to create links to aproach schools and listed heritage. Thus we propose the implementation of a civic, educational and cultural to be acomplished through a partnership with all related parts inspired with the same concern in active synergy. Accomplishing such formulations, the thesis maintains the significance of the heritage as well as the build-up of social identities, in accordance with the references of equity, law abiding, social justice, citzenship and public space. So that the stage for such achievements is formed by the instituitions, constructions as well as the abovementioned protagonists. At last, a special emphasis is given to a basic project envolving heritage education, to enable entrants to a knowledge of the listed heritage increasing those of the history of such heritage in the capacity of agents to reproduce their experience to their classmates, friends, family and the community they belong to.